THE INVASIVE MOSQUITO PROJECT - Thackrah, Ashley (My University, 2015)
My masters' project and field experience provided me with a variety of personal growth opportunities and taught me different aspects of the public health field. My capstone project developed a collection form and website for the Invasive Mosquito Project. One of my field experiences was with the Department of Public Health at the Fort Riley Army Installation and the other with the Riley County Health Department in Manhattan, Kansas. Principally my project and field experience focused on learning about mosquitoes and mosquito surveillance. Government funding for mosquito surveillance activities has decreased over the years, but mosquito-borne pathogens remain a major threat to humans. Despite the lack of support, mosquito surveillance is needed to track mosquito populations and administer adequate mosquito control measures. The Invasive Mosquito Project (IMP) fulfills this role. The IMP is a citizen science project that provides young students and teachers a portal to participate in a nationwide mosquito monitoring effort. The project provides educational materials for teachers including lesson plans, PowerPoint presentations, and protocols. Students collect mosquito eggs at their home and send them to a collection center for species identification. Various mosquito species spatial distribution will be defined as additional schools across the country participate in the program. In this report, I will discuss the project details and field experiences.
Keywords: Mosquito; Fort Riley; Mosquito-borne pathogens; Public Health (0573)